Book Review: Marine Protected Areas in International Law: an Arctic Perspective - Davina Oktivana (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2017)
Marine biodiversity has always become an interesting topic in the development of the law of the sea subject. Despite of human dependence on marine resources, human intervention has been proven as the major threats to the sustainability of marine biodiversity and marine environment protection. Human activities, such an over-exploitation, shipping pollution, the use endangered fishing tools and above all, climate change, have changes the ecosystems extensively. One of the significant measures to prevent broaden the catastrophe is the establishment of Marine Protected Areas (MPAs), which has been accepted as a tool for protection and conservation of marine biodiversity. The book provides a comprehensive observation and analysis of the MPAs' concept and its implementation, specifically in the Arctic. This book is based on Ingvild Ulrikke Jakobsen's PhD thesis at the University of Tromsø, Norwegia. Her concerned particularly based on the development of human activities in the Arctic, that will definitely affect the fragile marine environment and there is an increasing need to ensure environmental protection and conservation of marine biodiversity and ecosystems in Arctic.  DOI: https://doi.org/10.22304/pjih.v4n2.a11